CONTRIBUIÇÕES DE PAULO FREIRE PARA O DESPERTAR DO SUJEITO EPISTÊMICO NA EDUCAÇÃO MÉDICA: sob o viés do componente curricular Programa de Integração Escola, Serviço, Comunidade - Gonçalves Lima Bedim, Juçara; Correia dos Santos Moraes, Vivianne; Soares de Freitas Tamy, Mariana; de Almeida Luz, Clarisse (LINKSCIENCEPLACE, 2026)
The medical education adopted in Brazil has been undergoing significant debates especially referring to the need for changes in the curricular structure of the courses. As far as this situation/problem is concerned, it urges to resignify the teaching process, searching for innovative curricular orientations that meet the epistemological demands of contemporaneity in what concerns the integral health promotion of human beings. Therefore, the present paper, which is based on Paulo Freire’s libertarian/critical thinking linked to medical students’ formation, aims at consolidating the results obtained during cycles of lectures by students in the waiting room of Family Health Strategies Units. Such practice is developed through the curricular subject “Community, Service, School Integration Program” (PIESC) that is based on the adpotion of a new medical formation profile advocated by the National Curricular Guidelines for medical graduation. Action research was elected as methodology by means of which it was possible to contribute towards the solution of a collective problem in a collaborative and participative manner. The study is justified by the possibility of interconnecting medical students and the citizens served at the ESF, providing benefits to both groups, because besides the basic medical services provided, a collective reflection about the social autonomy deriving from knowledge is prioritized.